2019
DOI: 10.1177/1043659619872798
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Chinese Nursing Education and Practice for Developing International Nursing Partnerships

Abstract: Introduction: Modern nursing was introduced into China by Western missionaries in the 19th century; since then, significant changes continued to occur, which provides beneficial areas of international collaboration based on trends in globalization. Methods and Materials: The description was developed through reviews of published literature, policy documents that inform Chinese nursing practice, education, and the firsthand working experiences between American and Chinese nurses and faculty. Results: 82 article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In the era of rapid development of integrated media, technological innovation is constantly changing, and knowledge and information are also constantly being updated [41,42]. As teachers, we should keep up with the pace of the times, constantly update our concepts, boldly innovate, fully utilize various media and technological means, continuously improve teaching methods and methods, and practice teaching methods to be fexible and diverse [43][44][45]. Te "rain classroom" is gradually becoming a smart classroom teaching method in the feld of higher education.…”
Section: Introductionmentioning
confidence: 99%
“…In the era of rapid development of integrated media, technological innovation is constantly changing, and knowledge and information are also constantly being updated [41,42]. As teachers, we should keep up with the pace of the times, constantly update our concepts, boldly innovate, fully utilize various media and technological means, continuously improve teaching methods and methods, and practice teaching methods to be fexible and diverse [43][44][45]. Te "rain classroom" is gradually becoming a smart classroom teaching method in the feld of higher education.…”
Section: Introductionmentioning
confidence: 99%
“…However, the current textbooks in China focus on the cultivation of nurses’ clinical nursing ability and the teaching of medical knowledge [ 13 , 14 ]. In the education of nurses in China, there were relatively few specialized teaching materials on information education of nurses, focusing more on other aspects of nurse education [ 15 ]. The information literacy education of nurses often relied on the textbooks of medical information education, which was lack of professionalism of nursing information education [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers showed that China has played an increasing role in nursing research with the rapid development in nursing education and practice since the New Millennium (He, Fu, Su, & Luan, 2020;Kalisch & Liu, 2009;Li, Wei, Liu, & Tang, 2009;Li, 2014). Chinese people in the three major Chinese-speaking regions (ML, TW, and HK) have distinct political regimes, economic status, and health care systems, which lead to different scientific research productivity (Chair, Waye, Calzone, & Chan, 2019;Peng & Hui, 2011;Yan, Li, & McDonald, 2014).…”
Section: Introductionmentioning
confidence: 99%